If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + 4) * x(2x + 4) = 0 Reorder the terms: (4 + 2x) * x(2x + 4) = 0 Reorder the terms: (4 + 2x) * x(4 + 2x) = 0 Reorder the terms for easier multiplication: x(4 + 2x)(4 + 2x) = 0 Multiply (4 + 2x) * (4 + 2x) x(4(4 + 2x) + 2x * (4 + 2x)) = 0 x((4 * 4 + 2x * 4) + 2x * (4 + 2x)) = 0 x((16 + 8x) + 2x * (4 + 2x)) = 0 x(16 + 8x + (4 * 2x + 2x * 2x)) = 0 x(16 + 8x + (8x + 4x2)) = 0 Combine like terms: 8x + 8x = 16x x(16 + 16x + 4x2) = 0 (16 * x + 16x * x + 4x2 * x) = 0 (16x + 16x2 + 4x3) = 0 Solving 16x + 16x2 + 4x3 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '4x'. 4x(4 + 4x + x2) = 0 Factor a trinomial. 4x((2 + x)(2 + x)) = 0 Ignore the factor 4.Subproblem 1
Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0Subproblem 2
Set the factor '(2 + x)' equal to zero and attempt to solve: Simplifying 2 + x = 0 Solving 2 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + x = 0 + -2 x = 0 + -2 Combine like terms: 0 + -2 = -2 x = -2 Simplifying x = -2Subproblem 3
Set the factor '(2 + x)' equal to zero and attempt to solve: Simplifying 2 + x = 0 Solving 2 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + x = 0 + -2 x = 0 + -2 Combine like terms: 0 + -2 = -2 x = -2 Simplifying x = -2Solution
x = {0, -2, -2}
| 2*2+7y=14 | | 3+y=-5 | | 3k+5=3k+1 | | (7+v)(2v-5)=0 | | -2x+9=3x-1 | | 24+18x=12+24x | | 4(9b+4)= | | 20n-24=0 | | 10=y/4-8 | | -2(b-9)+4b-18=-6 | | -x^2+9x-20= | | y/5+2=8 | | -4/7x=21,8 | | 24v^2-12v=0 | | -x^8(3x^5-5)= | | 6x-3x=-9 | | x/7+6=4x-27 | | -x^2+37x-20= | | -4x-3(3+2x)=-19 | | 2x+7=26(6+x)-4 | | -17-4=7n-6(2+n) | | -(9x^2-3x+3)= | | y=n^2-2n-3 | | -3x-10=x+14 | | 6x-5=4x-27 | | f(x)=4x+3x-3 | | x^2+-12x+20= | | -2(-13+3y)-y=-5 | | -3+8=-5z+6(z+8) | | -6x+4+4x=2 | | -53=-6x-4x-3 | | -2(y+9)=-4y-22 |